Two dimensional Laplace transforms of generalized hypergeometric functions - R. S. Dahiya; I. H. Jowhar (International Journal of Mathematics and Mathematical Sciences)
The object of this paper is to obtain new operational relations between the original and the image functions that involve generalized hypergeometric G-functions.